Model Pemberdayaan Ekonomi Masyarakat Studi Kasus Wisata Desa Janari, Dusun Gatran, Desa Gondangsari, Kecamatan Pakis, Magelang: Model Pemberdayaan Ekonomi Masyarakat Studi Kasus Wisata Desa Janari, Dusun Gatran, Desa Gondangsari, Kecamatan Pakis, Magelang - Khuswatun Hasanah (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
This study aims to analyze the economic empowerment model of the community based on agriculture and tourism in Janari Village, Gatra Hamlet, Pakis District, Magelang. Using a qualitative approach, the study describes how the community leverages local potentials, such as vegetable and coffee crops, and integrates them into educational tourism. The younger generation plays a vital role in driving innovation, from managing agricultural products to digital marketing through social media and e-commerce. Challenges such as limited capital, weather, and pests are effectively addressed through strategies like crop diversification, intercroppingtechniques, and careful financial planning. Moreover, the development of educational tourism creates new market opportunities and increases community income without relying on middlemen. The implemented empowerment model demonstrates that combining local potential, technological innovation, and youth participation can build a self-sufficient and sustainable village economy. This study is expected to inspire other villages to optimize their local potentials effectively.